Comparison of Maximal Oxygen Uptake and Anaerobic Threshold in Soccer and Handball Players - Soyal Mehmet; Korkmaz Eryılmaz Selcen; Polat Metin; Aydoğan Sami (Physical Education of Students)
Ackground/Objective: The purpose of this study was to compare maximal oxygen uptake and anaerobic threshold values between soccer and handball players. Methods: 10 male professional soccer players and 10 male professional handball players took part in the study. Maximal oxygen uptake (VO2max) and anaerobic threshold (AT) were assessed using an incremental treadmill test. AT was estimated noninvasively using the V-slope method. The values of VO2 (ATVO2), heart rate (ATHR), time (ATTIME) and running speed (ATSPEED) corresponding to the AT were identified. AT was recorded as a percentage of VO2max (AT %VO2max) and HRmax (AT %HRmax). Time to exhaustion was determined as the total duration of the test. Results: There were no significant difference between the time to exhaustion(min), HRmax, absolute VO2max (ml min-1) and relative VO2max (ml kg-1min-1) of soccer and handball players compared to each other (p> 0.05). Similarly there were no significant difference between the two groups in the ATSPEED (km h-1), ATTIME (min), ATHR, absolute ATVO2 (ml min-1), relative ATVO2 (ml kg-1min-1), AT %VO2max and AT %HRmax (P> 0.05). Conclusion: Although soccer and handball require different movement patterns, they may exhibit similar aerobic endurance capacity. Hence physiological requirements in both branches may be expected to be similar in relation to training volume and intensity.